THE EFFECTIVENESS OF SMALL GROUP DISCUSSION TO IMPROVE STUDENTS' WRITING SKILLS: CASE OF NON-FORMAL EDUCATION STUDENTS - Hidayatullah, Nursidik; Barqy, Achmad Azam Al; Lestari, Hernina Dewi (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This study aims to investigate the extent to which students' writing skills can be promoted through small group discussions. A quasi-experimental study design was used. The analysis took place over six sessions, including pre-test, treatment, and post-test. There were two classes: A Class and B Class, each with 21 understudies. A Class was the control gather that was intense by address strategy, while B Class was the exploratory bunch that was intense through little bunch discourse. The information instrument was utilized in both the pre-test and the post-test. Both bunches were given the pre-test pre-test some time recently treatment started, and the post-test took put after treatment. The results indicated that the students in the test group scored higher on average (66 compared to 54) than the students in the control group. The result of the t-test calculation for independent samples showed a significance level of 0.000 and a p-value of 0.05. It is assumed that (Ha), while (Ho) is rejected due to the significance level < the value of probability (0.000 < 0.05). Therefore, BeTe (Be A Trainer) students in Desa Inggris Singosari who were taught writing in small group discussions experienced a significant improvement in their writing skills.